Keanekaragaman Tumbuhan Bawah Pada Tegakan Eucalyptus Pellita Di Fakultas Kehutanan Unilak Riau - Sri Rahayu Prastyaningsih; Anna Juliarti; Eni Suhesti; Syatrawati Syatrawati (Agriculture Faculty of Flores University, 2023)
This study aims to determine the understory in Eucalyptus pellita's stands. Understory are one of the elements of the ecosystem which are hold rainwater into the soil, prevent erosion, runoff and soil organic matter. The method used 20 x 20 m of 5 plots with 10 the number of sub-plots in the sample size of 2 x 2 m (50 sub-plots). All of understory were identified. There are 18 species from 17 families classified into 4 groups of the understory (grasses, sedges, ferns and broad-leaved plants). The results showed 18 types of understory which classified in 13 species of broadleaf plants, 3 species of grasses, 1 species of sedges and 1 species of ferns. The understory was dominated by Alang-Alang (Imperata cylindrica) with INP 61.33%, followed by Teki Grass (Cyperus sp) with INP 35.67% then Acacia (Acacia sp) with INP 21.67% and ferns (Neprolepsis sp) INP 17.8%. The Diversity of understory in Eucalyptus pellita was 1.76 in the medium category.